2018
DOI: 10.1186/s12890-018-0716-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of ambient air pollution on outpatient children with respiratory diseases in Shijiazhuang, China

Abstract: BackgroundAssociations between ambient air pollution and child health outcomes have been well documented in developed countries such as the United States; however, only a limited number of studies have been conducted in developing countries. This study aimed to explore the acute effects of five ambient air pollutants (inhalable particles [PM10], fine particles [PM2.5], sulfur dioxide [SO2], nitrogen dioxide [NO2] and 0zone [O3]) on children hospital outpatients with respiratory diseases in Shijiazhuang, China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 32 publications
9
33
3
1
Order By: Relevance
“…It is well known that air pollutants are the risk factors for many respiratory diseases in children. An eight-year time-series study in Hanoi showed that all air pollutants (PM 10 , PM 2.5 , NO 2 and SO 2 ) were positively associated with pneumonia, bronchitis and asthma hospitalizations among children [18], like that reported in Shijiazhuang [23] and Taiwan [9]. Consistent with these studies, we also found all air pollutants (except PM 10 ) were positively related to the outpatient visits of bronchitis and upper respiratory tract infection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is well known that air pollutants are the risk factors for many respiratory diseases in children. An eight-year time-series study in Hanoi showed that all air pollutants (PM 10 , PM 2.5 , NO 2 and SO 2 ) were positively associated with pneumonia, bronchitis and asthma hospitalizations among children [18], like that reported in Shijiazhuang [23] and Taiwan [9]. Consistent with these studies, we also found all air pollutants (except PM 10 ) were positively related to the outpatient visits of bronchitis and upper respiratory tract infection.…”
Section: Discussionsupporting
confidence: 89%
“…In stratification analysis, all of these outpatients were classified into different sex (boys and girls) and age (0-3 years, 4-6 years and 7-13 years), and season [cold season (November to March), hot season (June to August) and transition season (April, May, September and October)] [23,30]. According to the AIC and previous studies [23,31], the df of time was 3, 2, 3 per year for the cold, hot and transition season, respectively. We also conducted a sensitivity analysis by changing the df from 5 to 9 per year for calendar time and from 3 to 8 for temperature and relative humidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le et al demonstrated that in Ho Chi Minh City, Vietnam, hospital admissions of young children for acute lower respiratory infection were generally positively correlated with ambient levels of SO 2 during the dry season (November-April), but not the rainy season (May-October) [34]. In China, Song et al explored the acute effects of SO 2 on children's outpatient visits for respiratory diseases and found that a 10 µg/m 3 increase in the 2-day average concentration (lag01) of SO 2 corresponded to an increase of 0.33% (95% CI 0.10-0.56%) in daily hospital visits [35]. In addition to SO 2 pollution, we also explored the effect of NO 2 on the HFMD incidence.…”
Section: Discussionmentioning
confidence: 99%
“…There is a severe air pollution in China due to rapid economic development which led to implementation of series of measures to substitute solid fuel for clean energy (eg, electricity, gas, and solar energy) for cooking and heating in 28 cities to reduce air pollution and protect human health in 2017. However, the status of air pollution are still serious especially in northern rural areas . The main sources of outdoor air pollutants are anthropogenic activities such as the combustion of solid fuels predominantly involved in industrial processes and road traffic.…”
Section: Introductionmentioning
confidence: 99%